Regulating Pluralism: Laws on Religious Harmony and Possibilities for Robust Pluralism in Singapore - Neo, Jaclyn L. (The review of faith & international affairs, 2020)
This article examines the role of regulation in advancing a robust or “covenantal” pluralism in Singapore. I argue that a commitment to pluralism requires a regulated space where law provides a critical expressive role in setting out the boundaries of appropriate conduct as well as in modifying social norms. This is crucial to ensure that the dominant values of the religious majority do not hegemonize the common spaces to the exclusion of religious minorities. I examine the use of religious harmony laws in Singapore and its potential for framing the top-down aspect of the concept of covenantal pluralism.